2009
DOI: 10.1002/uog.6911
|View full text |Cite
|
Sign up to set email alerts
|

OP26.03: Vasa previa: prenatal diagnosis and neonatal outcome

Abstract: Objective: To derive indices describing the shape of the placenta, relationship of cord insertion to its centre and cord coiling in 200 term, singleton pregnancy placentas from an unselected population. Method: 200 consecutive unselected women were recruited with singleton pregnancy at 37-42 Weeks. Digital analysis of the placenta was performed using ''Image J'' (http://rsb.info.nih.gov/ij) software. Measurements were taken of the X and Y placental axes and, those intersecting the cord insertion. From these me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…The good outcome of the pregnancies with prenatally diagnosed vasa previa in this study is consistent with the findings of several other studies 4,7,8,10,14‐17 . Oyelese et al 4 found a lethality rate of 56% in pregnancies with undiagnosed vasa previa.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The good outcome of the pregnancies with prenatally diagnosed vasa previa in this study is consistent with the findings of several other studies 4,7,8,10,14‐17 . Oyelese et al 4 found a lethality rate of 56% in pregnancies with undiagnosed vasa previa.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Bergann et al report one fetal demise due to vasa previa curving at a distance from the internal cervical os. 7 This supports the inclusion in the definition of vasa previa of chorionic vessels in the proximity of the internal cervical os.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations